1994
DOI: 10.1093/clinids/18.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Early and Longitudinal Evaluations of Treated Infants and Children and Untreated Historical Patients with Congenital Toxoplasmosis: The Chicago Collaborative Treatment Trial

Abstract: Between December 1981 and May 1991, 44 infants and children with congenital toxoplasmosis were referred to our study group. A uniform approach to evaluation and therapy was developed and is described herein along with the clinical characteristics of these infants and children. In addition, case histories that illustrate especially important clinical features or previously undescribed findings are presented. Factors that contributed to the more severe disabilities included delayed diagnosis and initiation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
2
16

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(253 citation statements)
references
References 0 publications
10
223
2
16
Order By: Relevance
“…The effectiveness of treatment was not an outcome evaluated in this work, but the benefit of treatment in congenital toxoplasmosis has already been widely shown. [23][24][25] We stress that 17.6% of the patients studied presented active lesions at the time of the examination, which led us to add the use of corticosteroids in addition to the specific treatment of the disease to minimise the damage caused by the accompanying inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of treatment was not an outcome evaluated in this work, but the benefit of treatment in congenital toxoplasmosis has already been widely shown. [23][24][25] We stress that 17.6% of the patients studied presented active lesions at the time of the examination, which led us to add the use of corticosteroids in addition to the specific treatment of the disease to minimise the damage caused by the accompanying inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,[19][20][21][22] A significant reduction in prevalence and severity of the disease has been attributed to prenatal and neonatal treatment maintained throughout the first year of life. [23][24][25][26][27] However, there is currently an active discussion about the benefits of the treatment of congenital toxoplasmosis; it is thus important to know in detail the natural history of the disease. 28,29 The purpose of this work is to study the ocular manifestations in the first examination of confirmed cases of congenital toxoplasmosis in children under the age of 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…En neuroimágenes podemos encontrar calcificaciones intracraneales, hidrocefalia (generalmente secundaria al compromiso periacueductal), atrofia cortical y granulomas (9). En los casos uno y tres se requirió manejo quirúrgico por hidrocefalia.…”
Section: % (7)unclassified
“…Las dosis óptimas y la duración del tratamiento no se ha establecido definitivamente hasta la actualidad, pero la bibliografía sugiere: pirimetamina 2 mg / kg durante dos días, y luego 1 mg / kg por seis meses, y después 1 mg / kg interdiario hasta completar un año, además de sulfadiazina 100 mg / kg/d durante un año, más leucovorina 10 mg tres veces por semana durante y después de una semana de terapia con pirimetamina, este requimen se asocia con disminución de las complicaciones a largo plazo y disminución de las oftalmopatías de nueva aparición en comparación con ningún tratamiento o con tratamientos de corta duración (3,9,12). También se sugiere añadir glucocorticoides (prednisona 1 mg/kg/d) si el LCR tiene más de 1 g / dl de proteínas o si hay evidencia de coriorretinitis activa (9). La pirimetamina debe interrumpirse temporalmente si el recuento absoluto de neutrófilos cae por debajo de 500 células / microlitro.…”
Section: Rev Neuropsiquiatr 77 (3) 2014unclassified
“…Although most cases are subclinical, manifestations can be broad-ranging with sequelae unrecognised for decades 23 . Outcomes may include spontaneous abortion, still birth or prematurity, or manifestations such as 23,24 .…”
mentioning
confidence: 99%